2016
DOI: 10.15171/hpp.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Oral health education program among pre-school children: an application of health-promoting schools approach

Abstract: Background: Preschool children have a limit ability to take care of their teeth. The aim of this study was to determine the effect of an intervention based on Albanian’s Health Promoting Schools Model (Albanian’s HPSM) on the oral health behaviors among a group of Iranian female preschool (5-6 years old) children. Methods: In this quasi-experimental study, 120 children in seventh district of Tehran, Iran were randomly recruited and assigned to either the intervention or the control groups. A scale was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
18
0
4
Order By: Relevance
“…In the study of Babaee et al on students aged 12-14 and in that of Sanadhya et al on students aged 12-15, oral and dental health education improved the mean score of students' knowledge [27,28]. In the study of Shirzad et al an educational intervention could change the attitude of mothers and teachers towards students' brushing [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Babaee et al on students aged 12-14 and in that of Sanadhya et al on students aged 12-15, oral and dental health education improved the mean score of students' knowledge [27,28]. In the study of Shirzad et al an educational intervention could change the attitude of mothers and teachers towards students' brushing [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies 9-11 performing health education practices with preschool children required the adoption of playing strategies such as stories, painting, games, and puzzles in order to promote healthy behaviors related to personal hygiene. A study conducted with 78 preschool children (2-6 years old) adopted playful strategies such as games, cartoons, drawing, and interaction with an adult dressed as a superhero during 12 months in a Brazilian kindergarten found that 62.7% of children learned about how to prevent anemia and had healthier eating habits encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the need for health education practices in educational settings, previous studies investigated the effectiveness of interventions to promote oral health, 9 healthy eating behaviors 10 and hand washing 11 in preschool children. However, evidence regarding the effects of an educational playful intervention on healthy nasal hygiene behaviors in children aged 3-4 years attending a daycare center remains unmet.…”
Section: Introductionmentioning
confidence: 99%
“…La Técnica Expositiva consiste en una charla-coloquio sobre el tema a tratar y un momento para que los asistentes expresen sus dudas u opiniones. La charla va acompañada de recursos didácticos que deben poseer coherencia, ser atractivos, concretos y comunicativos [37][38][39] . La Técnica Demostrativa es un método dinámico en el que el educador explica y lleva a la práctica una habilidad psicomotora.…”
Section: Second Stage: Educational Interventionunclassified
“…The Expository Method consists of carrying out an exposition about the topic to be discussed, followed by questions or opinions from the attendees. The discussion is supported by educational resources which must be coherent, attractive, concrete and communicative [37][38][39] . The Demonstrative Method is a dynamic technique in which the educator explains and puts into practice a psychomotor skill, the group is requested to replicate that skill and thus a training process is established 38 .…”
mentioning
confidence: 99%